The time constant of the somatogravic illusion - Correia Grácio, B. J.; de Winkel, K. N.; Groen, E. L.; Wentink, M.; Bos, J. E. (Experimental brain research, 2013)
Without visual feedback, humans perceive tilt when experiencing a sustained linear acceleration. This tilt illusion is commonly referred to as the somatogravic illusion. Although the physiological basis of the illusion seems to be well understood, the dynamic behavior is still subject to discussion. In this study, the dynamic behavior of the illusion was measured experimentally for three motion profiles with different frequency content. Subjects were exposed to pure centripetal accelerations in the lateral direction and were asked to indicate their tilt percept by means of a joystick. Variable-radius centrifugation during constant angular rotation was used to generate these motion profiles. Two self-motion perception models were fitted to the experimental data and were used to obtain the time constant of the somatogravic illusion. Results showed that the time constant of the somatogravic illusion was on the order of two seconds, in contrast to the higher time constant found in fixed-radius centrifugation studies. Furthermore, the time constant was significantly affected by the frequency content of the motion profiles. Motion profiles with higher frequency content revealed shorter time constants which cannot be explained by self-motion perception models that assume a fixed time constant. Therefore, these models need to be improved with a mechanism that deals with this variable time constant. Apart from the fundamental importance, these results also have practical consequences for the simulation of sustained accelerations in motion simulators.